Progress in Mycotoxins Affecting Intestinal Mucosal Barrier Function - Ren, Zhihua (Int J Mol Sci, 2019)
Mycotoxins, which are widely found in feed ingredients and human food, can exert harmful effects on animals and pose a serious threat to human health. As the first barrier against external pollutants, the intestinal mucosa is protected by a mechanical barrier, chemical barrier, immune barrier, and biological barrier. Firstly, mycotoxins can disrupt the mechanical barrier function of the intestinal mucosa, by destroying the morphology and tissue integrity of the intestinal epithelium. Secondly, mycotoxins can cause changes in the composition of mucin monosaccharides and the expression of intestinal mucin, which in turn affects mucin function. Thirdly, mycotoxins can cause damage to the intestinal mucosal immune barrier function. Finally, the microbiotas of animals closely interact with ingested mycotoxins. Based on existing research, this article reviews the effects of mycotoxins on the intestinal mucosal barrier and its mechanisms.